2018
DOI: 10.1177/2309499018799520
|View full text |Cite
|
Sign up to set email alerts
|

Is restricted hip movement a risk factor for anterior cruciate ligament injury?

Abstract: Restricted hip movement along with femoroacetabular impingement (FAI) has been reported to be an important risk factor in anterior cruciate ligament (ACL) injury. We performed a literature review assessing the evidence that FAI, or restricted hip movement, contributes to the likelihood of sustaining an ACL injury to provide an evidence-based and comprehensive update on the relationship between these pathologies. Studies were divided into three categories: clinical studies, radiological studies and cadaveric st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As already noted, there is no biomechanical factor that is really a demonstrable cause to conclude that, as in other sports such as basketball, handball, volleyball or football, the risk of ACL injury is higher in women than in men [5][6][7]35]. This is probably due to the way in which they occur.…”
Section: Discussionmentioning
confidence: 95%
“…As already noted, there is no biomechanical factor that is really a demonstrable cause to conclude that, as in other sports such as basketball, handball, volleyball or football, the risk of ACL injury is higher in women than in men [5][6][7]35]. This is probably due to the way in which they occur.…”
Section: Discussionmentioning
confidence: 95%
“…The restriction of hip ROM will impose strong rotational force on the knee joint, leading to the increased strain of the ACL accompanying the risk of ACL fatigue failure and therefore, a higher rate of ACL tear (13,15,35,37). In line with this potential mechanism of ACL injury, several cadaveric studies have demonstrated that peak ACL strain was inversely related to the range of internal rotation of the femur (38).…”
Section: Discussionmentioning
confidence: 99%
“…The hip impingement is an anatomical condition often associated with a predisposition to ACL rupture and thus a higher risk of failure of ACL-R. It is accompanied by limited ROM, especially during internal rotation, simulating a pivot landing on the ipsilateral knee, which therefore increases stress on the ACL ( 60 , 61 ).
Figure 2 Stenotic, very small notch with a vertical, non-anatomical graft.
…”
Section: Reasons Of Failurementioning
confidence: 99%